1968
DOI: 10.1139/o68-139
|View full text |Cite
|
Sign up to set email alerts
|

Sources of sulfur in the thioglucosides of various higher plants

Abstract: L-Methionine-35S and DL-cysteine-35S were good sources of sulfur for the biosynthesis of sinigrin in Armoracia lapathifolia Gilib. and were incorporated with approximately the same efficiency. Homomethionine-35S was a slightly poorer source of sulfur than methionine, while taurine-35S was a very poor source. When homomethionine, methionine, and cysteine were employed as sources of sulfur, the distribution of radioactivity between the two sulfur atoms in sinigrin was approximately 80% in the isothiocyanate moie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…CYP83B1 N-hydroxylates indole-3-acetaldoxime to the corresponding aci-nitro compound, 1-aci-nitro-2-indolyl-ethane Hansen et al, 2001;Naur et al, 2003). This compound is conjugated with an S-donor, most likely Cys (Wetter and Chisholm, 1968). The respective genes and enzymes are not yet known (Halkier and Gershenzon, 2006).…”
Section: Discussion the Role Of Cyp81f2 In The Biosynthesis Of Modifimentioning
confidence: 99%
“…CYP83B1 N-hydroxylates indole-3-acetaldoxime to the corresponding aci-nitro compound, 1-aci-nitro-2-indolyl-ethane Hansen et al, 2001;Naur et al, 2003). This compound is conjugated with an S-donor, most likely Cys (Wetter and Chisholm, 1968). The respective genes and enzymes are not yet known (Halkier and Gershenzon, 2006).…”
Section: Discussion the Role Of Cyp81f2 In The Biosynthesis Of Modifimentioning
confidence: 99%
“…First, in vivo feeding studies have shown that among other sulfur donors, cysteine is most efficiently incorporated into glucosinolates (23). Second, the enzyme that converts S-alkyl thiohydroximate to thiohydroximate is likely to be a C-S lyase, and the characterized C-S lyases from plants hydrolyze Ssubstituted cysteine derivatives and have an absolute requirement for the presence of the ␣-hydrogen atom and an unsubstituted amino group in the cysteine moiety (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, worth mentioning that despite an advanced understanding of the glucosinolate pathway at the biochemical level, the source of reduced sulphur in the glucosinolate structure has remained elusive and was thought to be cysteine for decades (Geu-Flores et al 2011;Sønderby et al 2010). This assumption was mainly based on feeding experiments using 35 S-labelled cysteine in which the radiolabelled S from cysteine was found to be more efficiently incorporated into glucosinolates compared to radiolabelled S from methionine or thioglucose (Wetter and Chisholm 1968). Such experiments, however, were inconclusive due to the incorporation of the label into GSH even in the presence of the γ-Glu-Cys synthetase inhibitor buthionine sulfoximine (Bednarek et al 2009;Schlaeppi et al 2008).…”
Section: Biosynthesis Of Glucosinolatesmentioning
confidence: 99%